Promoting recovery from severe mental illness: Implications from research on metacognition and metacognitive reflection and insight therapy - Lysaker, Paul Henry (World J Psychiatry, 2018)
Research indicates that individuals with schizophrenia recover. Recovery, however means different things to different individuals and regardless of what kind of experiences define recovery, the individual diagnosed with the serious mental illness must feel ownership of their recovery. This raises the issue of how mental health services should systematically promote recovery. This paper explores the practical implications for research on metacognition in schizophrenia for this issue. First, we present the integrated model of metacognition, which defines metacognition as the spectrum of activities which allow individual to have available to themselves an integrated sense of self and others as they appraise and respond to the unique challenges they face. Second, we present research suggesting that many with schizophrenia experience deficits in metacognition and that those deficits compromise individuals’ abilities to manage their lives and mental health challenges. Third, we discuss a form of psychotherapy inspired by this research, Metacognitive Reflection and Insight Therapy which assists individuals to recapture the ability to form integrated ideas about themselves and others and so direct their own recovery. The need for recovery oriented interventions to focus on process and on patient’s purposes, assess metacognition and consider the intersubjective contexts in which this occurres is discussed.